Penerapan Data Mining Dalam Pengelompokkan Buku Yang Dipinjam Menggunakan Algoritma K-Means - Herlina Latipa Sari; Ila Yati Beti (STMIK Budi Darma, 2023)
The purpose of this study is to apply data mining in grouping books that are borrowed based on the number of available books, so that by implementing data grouping with the k-means algorithm it will determine the books that are most in demand as seen from the number of available books, books read, and books borrowed from the Dehasen Bengkulu University Library. Data mining is a process or activity carried out to collect large data and then extract the data so that it becomes information that can be used for something useful. From the results of applying data mining to grouping book titles borrowed at the Dehasen Bengkulu University library using the k-means algorithm which has been applied the book titles have been grouped into 2 clusters according to the specified criteria, namely the number of books available, the number of books read and the number of books read. borrowed with the calculation results shown from cluster I (high) from the k-means data grouping there are 10 the number of codes and book titles with the number of books available being 295 with the average number of books read being 9 books and the average number of books read 11 books were borrowed and in cluster II (low) of the k-means data grouping there were 10 numbers of codes and book titles with 115 available books with an average number of books read 5 books and an average number of books borrowed as many as 4 books.